The design of business : why design thinking is the next competitive advantage - Martin, Roger L. (Boston, Mass. : Harvard Business Press, 2009)
Most companies today have innovation envy. Many make genuine efforts to be innovative: they spend on R & D, bring in creative designers, hire innovation consultants; but they still get disappointing results. Roger Martin argues that to innovate and win, companies need 'design thinking'.
The knowledge funnel : how discovery takes shape -- The reliability bias : why advancing knowledge is so hard -- Design thinking : how thinking like a designer can create sustainable advantage -- Transforming the corporation : the design of Procter & Gamble -- The balancing act : how design-thinking organizations embrace reliability and validity -- World-class explorers : leading the design-thinking organization -- Getting personal : developing yourself as a design thinker.
Includes bibliographical references.
Description based on online resource; title from electronic title page (ProQuest Ebook Central, viewed February 16, 2018).
Master record variable field(s) change: 050
Keywords: Creative ability in business; Lateral thinking; Creative thinking; Knowledge management; Management; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Creative ability in business; Creative thinking; Knowledge management; Lateral thinking; Management; Unternehmen; Kreatives Denken; Wissensmanagement; Wettbewerbsvorteil; elektronické knihy; electronic books